2010
DOI: 10.1123/jis.3.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mental Toughness in NCAA Athletes

Abstract: The purpose of the current study was to explore National Collegiate Athletic Association (NCAA) Division 1 athletes' perceptions of mental toughness. Specifically, three areas of mental toughness were explored including attributes, the role of significant others, and strategies used to build mental toughness. In-depth interviews were conducted with 15 athletes from a variety of sports. Lower and higher-order themes were developed to capture the main ideas of mental toughness. Various psychological attributes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 13 publications
1
44
0
3
Order By: Relevance
“…This capacity has been discussed as a collection of personal characteristics including attributes such as self-confidence, optimistic thinking, and psychological resilience, leading to a general consensus that mental toughness is a multidimensional concept (Butt et al, 2010;Jones et al, 2002). In testing this assumption regarding the dimensionality of mental toughness, Gucciardi et al (in press) found that there was considerable empirical overlap among such personal characteristics and that a multidimensional construct was limited in terms of discriminant validity.…”
Section: Mental Toughness In Sportmentioning
confidence: 99%
See 4 more Smart Citations
“…This capacity has been discussed as a collection of personal characteristics including attributes such as self-confidence, optimistic thinking, and psychological resilience, leading to a general consensus that mental toughness is a multidimensional concept (Butt et al, 2010;Jones et al, 2002). In testing this assumption regarding the dimensionality of mental toughness, Gucciardi et al (in press) found that there was considerable empirical overlap among such personal characteristics and that a multidimensional construct was limited in terms of discriminant validity.…”
Section: Mental Toughness In Sportmentioning
confidence: 99%
“…Mental toughness is a term that is often used to describe a collection of psychological characteristics thought to be central to high performance (Butt et al, 2010;Jones et al, 2002). Over the last decade, researchers have expended considerable efforts in attempting to define and conceptualize mental toughness.…”
Section: Chapter III Mental Toughness In Sport: Motivational Antecedmentioning
confidence: 99%
See 3 more Smart Citations